The visual-based robotic language for industry 4.0 applications: Robotic U Language - Sakarya, Ufuk (SPRINGER LONDON LTD, 2024)
In this article, a visual-based robotic language is proposed for the management of mobile robots, which is an important element of the new industrial revolution. Efficient management of artificial intelligence robots within industry 4.0 applications is an important problem. Thanks to the use of the proposed language, it is aimed to increase the energy efficiency of mobile robots. The proposed visual-based robot language has a two-dimensional structure, but it is not actually an image by its nature. It is a visual-based code designed to provide a solution to the blurring problem in image-based visual coding. The proposed method basically consists of rods and is a coding based on arranging rods of varying lengths in a two-dimensional plane. According to the presented experimental studies, the robustness of the proposed visual-based robotic language against blurring has been demonstrated.
Keywords: Industry 4; 0 applications; Visual-based code; Mobile robots; Robotic U Language; Engineering; Imaging Science & Photographic Technology